Synthetic Stimuli for the Steady-State Verification of Modulation-Based Noise Reduction Systems. (7th April 2009) - Lamm Lamm, Jesko G. Jesko G.; Berg Berg, Anna K. Anna K.; Glück Glück, Christian G. Christian G.
Abstract : Hearing instrument verification involves measuring the performance of noise reduction systems. Synthetic stimuli are proposed as test signals, because they can be tailored to the parameter space of the noise reduction system under test. The article presents stimuli targeted at steady-state measurements in modulation-based noise reduction systems. It shows possible applications of these stimuli and measurement results obtained with an exemplary hearing instrument.